Does stock market capitalization cause GDP? A causality study for Central and Eastern European countries - María Asuncíon Prats Albentosa; Beatriz Sandoval (Kiel Institute for the World Economy (IfW), 2019)
This paper analyses the relationship between stock market capitalization and real GDP in ten Central and Eastern European countries (CEECs) that joined the European Union in 2004 and 2007, with the objective of determining if the financial markets have played a role as a driver of the economic development in these countries or vice versa. The methodology is based on the application of three different measures of causality between the relevant variables, in order to determine the existence and the direction of causality. Using a cointegrated Vector Autoregressive model (VAR), the authors study the relationship between the relevant variables through the following tests: Granger causality test, Toda-Yamamoto approach and Frequency Domain approach. The results obtained suggest evidence of the existence of this relationship, in both directions, in a significant number of this group of countries, and especially in those there is a long-term relationship.
https://doi.org/10.7910/DVN/IWQKSP
Keywords: C32; F43; G15; 330; stock market development; economic growth; Granger causality; Toda-Yamamoto; Frequency Domain